PedsQL™ Gastroparesis Symptoms Module Domain and Item Development: Qualitative Methods. Issue 2 (August 2021) - Varni, James W.; Shulman, Robert J.; Self, Mariella M.; Febo-Rodriguez, Liz; Charron, Heather; Williams, Kent; Nurko, Sam; Rosen, Rachel L.; Chumpitazi, Bruno P.
ABSTRACT: Objectives: Like adults, children suffer from gastroparesis; however, there are currently no validated instruments to determine the impact of gastroparesis in pediatric patients. The objective of this study was to develop the items and domains to support the content validity of the new Pediatric Quality of Life Inventory (PedsQL™) Gastroparesis Symptoms Module. Methods: Patients were recruited from the National Institute of Diabetes and Digestive and Kidney Diseases Pediatric Gastroparesis Registry. The qualitative methods involved an iterative process comprising a literature review of existing questionnaires and gastroparesis clinical research, an expert review panel of pediatric gastroenterologists who provided feedback on the conceptual framework in developing the semi-structured interview, and in-depth focus interviews with six pediatric patients with gastroparesis and five of their parents (one did not participate) in developing relevant domains and item content. In the subsequent cognitive interviews phase, five additional patients with gastroparesis and their parents provided detailed feedback on item content, relevance, importance, and understandability of the domains and items. Results: Ten domains/scales were derived from the qualitative methods, with item content saturation achieved at 67 items, with no further themes or content identified during the final cognitive interviews. The Module is comprised of 10 individual scales measuring nausea, stomach fullness when eating, vomiting, dry heaves, heartburn and reflux, stomach pain and hurt, food and drink limits, bloating, appetite, and worry. Conclusions: Our study supports the content validity of the new PedsQL Gastroparesis Symptoms Module. The Module field test study will be conducted in a multisite national study. Abstract : Supplemental Digital Content is available in the text